468 IMPROVING ADVANCE CARE PLANNING SKILLS IN JUNIOR DOCTORS. (14th June 2021) - Cohen, S; Singh, R; Khalid, N; Young, J; Aldiwani, M; Roy, D; Edwards, I
Abstract: Introduction: Junior doctors are increasingly encountering Advance Care Planning (ACP) when they look after frail, older or multi-morbid patients during their hospital rotations. However, there remains a lack of formal training and resources, particularly with DNACPR discussions and when engaging patients and their loved ones with Emergency Health Care Planning (EHCP). We aimed to assess the need for ACP, improve the infrastructure by which ACP is delivered, and better support junior doctors to have these difficult conversations. Method: Discharges from the Geriatrics Department at Kettering General Hospital were reviewed initially in May 2019 and again in January 2020 following intervention. We introduced a focused communication skills training session delivered at departmental teaching, which included a combination of simulation training and lectures. We additionally designed and implemented an EHCP template to aid junior doctors' discussions. This could also be copied to the discharge letter, to facilitate safe transfer of care to primary care. Results: In May 2019 of 32 patients, 100% met at least one SPICTTM criterion, with median of 4 criteria, thus indicating a high need for ACP in this cohort. Despite this, only one discharge letter included an EHCP and two had a request for GP colleagues to complete one. Evaluation of discharges again in January of 2020 reconfirmed a similar need for ACP, but following our interventions, the number of EHCP's performed had increased. Of 22 identified patients 4 had a completed EHCP and 3 were requested for completion by their GP. Qualitative questionnaires demonstrated an improvement in both knowledge and confidence amongst junior doctors following the training session. Conclusion: We have shown that there is a necessity for ACP to be considered for Geriatrics inpatients, and that providing structure and training in this challenging area offers benefit to both patients and junior doctors.